The Effect of Pattern and Infill Percentage in 3D Printer for Phantom Radiation Applications - Hariyanto, Aditya Prayugo; Christianti, Kurnia Hastu; Rubiyanto, Agus; Nasori, Nasori; Haekal, Mohammad; Endarko, Endarko (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
3D printing technology was capable of fabricating phantoms to enhance quality assurance in radiation therapy. The ideal phantom has properties equivalent to the real tissue. However, 3D Printing has the limits to mimicking the attenuation properties of various tissues because during 3D printing there can be only one type of material. The purpose of this study was to evaluate the effect of infill percentage and infill patterns of 3D printing technology to simulate various types of tissue. This study used 25 samples measuring 5 × 5 × 1 cm3 from PETG material. The 20 samples were printed using variations infill percentages from 5 - 100% and the infill pattern in lines. The five samples were then printed with the infill percentage constant at 50% and used the infill pattern triangles, grid, gyroid, octet, and concentric. We used Computed Tomography (CT) to determine the Hounsfield Unit (HU) value for each sample and evaluated the suitability of each sample for phantom applications in radiation therapy and radiology. However, none of the samples was able to simulate compact bone. As a result, we found that PETG material could simulate the properties of soft tissue, fat, lung, kidney, liver, pancreas, and spongy bone. Thus, the study had shown promising potential for the fabrication of the anthropomorphic phantom of radiation therapy.